The Effect of Solar Energy on the Environmental Impacts and Sustainability of Food Industry - Martzopoulou, Anastasia; Komninos, Nicos (Journal of Environmental Accounting and Management, 2026)
The agri-food sector is in front of the great challenge of decoupling its economic growth from energy consumption. This research work investigates the effect of energy sources on the environmental impacts and sustainability of food industries in Greece as a case study. The emergy analysis was used as a supporting action tool for the diagnosis and the benchmarking of food industries in terms of their sustainability and environmental impacts, according to the available source of energy. The energy sources examined are from conventional sources and solar energy, the most available renewable energy source in Greece. All the inputs and outputs of the food industrial activity were applied, highlighting the interaction between sustainable development, environmental impact and competitiveness. In this study,it was found that the exploitation of solar energy by the examined food manufacturing industries contributes to the reduction of the environmental impact by up to 20.4% and the increase of their sustainability by 39.7%, in comparison to those of conventional energy sources. Also, an improvement of 7.3%in the emergy index of competitiveness was observed with out necessarily requiring a reduction in labour input, which may mean either paycut or a reduction in human resources. Finally, an improved algorithm of the Environmental Loading Ratio indexis calculated and a new emergy index, the Emergy eco-Productivity Indexis introducedin this work. The latter is increased up to 45.85% with the contribution of solar energy and expresses the inﬂuence of the monetary, non-monetary and renewable sources in the ﬁnal economic product.